Wajib Daftar Usaha Bagi Pelaku Usaha E-commerce Menurut Undang-undang Nomor 7 Tahun 2014 Tentang Perdagangan (JURNAL HUKUM SEHASEN, 2017)
Enterprises / bisnise-commerce has many moldy in Indonesia, we would have seen an offline business which is then marketed e-commerce to boost sales or to be famous. business e-commerce is certainly a business that is run through the internet media. Everyone who has an internet connection and also have products to sell in e-commerce can run a business e-commerce. The target market is not limited because it can sell products anywhere both local and International. Business e-commerce in Indonesia is not specifically regulated in the Act. No ordinance, transaction requirements, requirements for the establishment, the tax to be paid and other matters that regulate this activity. However, to minimize crime in the business of e-commerce, the government has made the Law on Information and Electronic Transactions (UU ITE) No. 11 of 2008. In addition to reducing the risk of e-commerce businesses that do not provide good consumer rights, the government formulates regulations rules in order to protect the transactions made by buyers and sellers in Act No. 7 of 2014 About the trade that every business needs to have a business license (original). Interest diharuskannya register the company, that the government can prepare and establish policy in order to provide guidance, supervision and oversight of the business world at a time can be used as security for the state revenue in creating healthy business science and orderly. The government will also be easy to occasionally follow carefully the circumstances and the actual development of the business and the company, in this thesis will discuss how setting trade license e-commerce pursuant to Law No. 7 Tahun2014 on Trade, and the way law enforcement mandatory list of business for the business e-commerce.